Improved clonality assessment in germinal centre/post-germinal centre non-Hodgkin's lymphomas with high rates of somatic hypermutation. Issue 5 (30th June 2006) - Catherwood, Mark A; Gonzalez, David; Patton, Caroline; Dobbin, Edwina; Venkatraman, Lakshmi; Alexander, H Denis
Abstract : Background: PCR detects clonal rearrangements of the Ig gene in lymphoproliferative disorders. False negativity occurs in germinal centre/post-germinal centre lymphomas (GC/PGCLs) as they display a high rate of somatic hypermutation (SHM), which causes primer mismatching when detecting Ig rearrangements by PCR. Aims: To investigate the degree of SHM in a group of GC/PGCLs and assess the rate of false negativity when using BIOMED-2 PCR when compared with previously published strategies. Methods: DNA was isolated from snap-frozen tissue from 49 patients with GC/PGCL (23 diffuse large B cell lymphomas (DLBCLs), 26 follicular lymphomas (FLs)) and PCR-amplified for complete (VDJH), incomplete (DJH) and Igκ/λ rearrangements using the BIOMED-2 protocols, and compared with previously published methods using consensus primers. Germinal centre phenotype was defined by immunohistochemistry based on CD10, Bcl-6 and MUM-1. Results: Clonality detection by amplifying Ig rearrangements using BIOMED-2 family-specific primers was considerably higher than that found using consensus primers (74% DLBCL and 96% FL vs 69% DLBCL and 73% FL). Addition of BIOMED-2 DJH rearrangements increased detection of clonality by 22% in DLBCL. SHM was present in VDJH rearrangements from all patients with DLBCL (median (range) 5.7% (2.5–13.5)) and FL (median (range) 5.3% (2.3–11.9)) with a clonal rearrangement. Conclusions: Use of BIOMED-2 primers has significantly reduced the false negative rate associated with GC/PGCL when compared with consensus primers, and the inclusion of DJH rearrangements represents a potential complementary target for clonality assessment, as SHM is thought not to occur in these types of rearrangements.